2015
DOI: 10.4037/ajcc2015123
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressors and Development of Pressure Ulcers in Adult Critical Care Patients

Abstract: Background Vasopressors are lifesaving agents used to raise mean arterial pressure in critically ill patients in shock states. The pharmacodynamics of these agents suggest vasopressors may play a role in development of pressure ulcers; however, this aspect has been understudied. Objective To examine associations between type, dose, and duration of vasopressors (norepinephrine, epinephrine, vasopressin, phenylephrine, dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
103
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 35 publications
9
103
0
10
Order By: Relevance
“…[10][11][12][13] Some physiological (intrinsic) and nonphysiological (extrinsic) risk factors that may place adults at risk for pressure ulcer development are advanced age; comorbid conditions including diabetes mellitus, peripheral vascular disease, cerebral vascular accident, sepsis, cardiovascular disease, and hypotension; severity of illness (as indicated by Acute Physiology and Chronic Health Evaluation [APACHE] IV score) 14 ; and iatrogenic factors such as the use of vasopressors. 11,12,15 A hypothesis exists that these physiological risk factors place the patients at risk because of impairment of the microcirculation system. 16 Microcirculation is controlled in part by central sympathetic vasoconstrictor impulses from the brain and secretions from localized endothelial cells.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[10][11][12][13] Some physiological (intrinsic) and nonphysiological (extrinsic) risk factors that may place adults at risk for pressure ulcer development are advanced age; comorbid conditions including diabetes mellitus, peripheral vascular disease, cerebral vascular accident, sepsis, cardiovascular disease, and hypotension; severity of illness (as indicated by Acute Physiology and Chronic Health Evaluation [APACHE] IV score) 14 ; and iatrogenic factors such as the use of vasopressors. 11,12,15 A hypothesis exists that these physiological risk factors place the patients at risk because of impairment of the microcirculation system. 16 Microcirculation is controlled in part by central sympathetic vasoconstrictor impulses from the brain and secretions from localized endothelial cells.…”
mentioning
confidence: 99%
“…Because neural and endothelial control of blood flow is impaired during an illness state, the patient may be more susceptible to ischemic organ damage (eg, pressure ulcers). [15][16][17] Additional risk factors that have been correlated with pressure ulcer development are smoking history, dry skin, low body mass index, impaired mobility, altered mental status (ie, confusion), urinary and fecal incontinence, and malnutrition. 15,17,18 Although research has indicated that many of these factors are significantly related to the development of HAPUs in ICU patients, the findings were not consistent in all of the studies in which these relationships were tested.…”
mentioning
confidence: 99%
See 3 more Smart Citations